Looking closely inside the garden - Serafini, Frank (Tonawanda, NY : Kids Can Press, 2008)
Up-close photographs and simple text describe the plants, animals, and insects that inhabit a garden.
3.5
K-3
Keywords: Garden animals -- Juvenile literature; Photography, Close-up -- Juvenile literature; Plants -- Juvenile literature; Garden animals; Photography, Close-up.; Plants; Close-up photography; Garden animals; Plants